Social capital and the decline in HIV transmission - A case study in three villages in the Kagera region of Tanzania - Gasto Frumence; Japhet Killewo; Gideon Kwesigabo; Lennarth Nyström; Malin Eriksson; Maria Emmelin (Taylor & Francis Group, 2010)
We present data from an exploratory case study characterising the social capital in three case villages situated in areas of varying HIV prevalence in the Kagera region of Tanzania. Focus group discussions and key informant interviews revealed a range of experiences by community members, leaders of organisations and social groups. We found that the formation of social groups during the early 1990s was partly a result of poverty and the many deaths caused by AIDS. They built on a tradition to support those in need and provided social and economic support to members by providing loans. Their strict rules of conduct helped to create new norms, values and trust, important for HIV prevention. Members of different networks ultimately became role models for healthy protective behaviour. Formal organisations also worked together with social groups to facilitate networking and to provide avenues for exchange of information. We conclude that social capital contributed in changing HIV related risk behaviour that supported a decline of HIV infection in the high prevalence zone and maintained a low prevalence in the other zones.